2021
DOI: 10.1007/s11211-021-00362-3
|View full text |Cite
|
Sign up to set email alerts
|

Autochthony Belief and Making Amends to Indigenous Peoples: The Role of Collective Moral Emotions

Abstract: Intergroup relations in settler societies have been defined by historical conflict over territorial ownership between indigenous peoples and settler majorities. However, the indigenous groups were there first, and first arrival is an important principle for assigning ownership to a group. In two studies among Australians of Anglo-Celtic origin (N = 322 and N = 475), we argued and found that the general belief in entitlements for first comers (i.e. autochthony) is related to more support for reparations in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 70 publications
(101 reference statements)
0
17
0
Order By: Relevance
“…Autochthony belief was measured with three items that have been previously used in research on autochthony in the Netherlands (Martinovic & Verkuyten, 2013), Great Britain (Nijs, Martinović et al, 2021), and Australia (Nooitgedagt, Martinović et al, 2021): “Every territory belongs primarily to its first inhabitants.”, “Those who arrived first in a territory can be considered to own it more.”, and “‘We were here first’ is a good argument for determining who owns the territory.”…”
Section: Methodsmentioning
confidence: 99%
“…Autochthony belief was measured with three items that have been previously used in research on autochthony in the Netherlands (Martinovic & Verkuyten, 2013), Great Britain (Nijs, Martinović et al, 2021), and Australia (Nooitgedagt, Martinović et al, 2021): “Every territory belongs primarily to its first inhabitants.”, “Those who arrived first in a territory can be considered to own it more.”, and “‘We were here first’ is a good argument for determining who owns the territory.”…”
Section: Methodsmentioning
confidence: 99%
“…This finding is surprising, as we anticipated the autochthony principle to be exclusive. Previous research in settler societies found that settlers’ endorsement of the autochthony principle was associated with perceiving the indigenous outgroup as owners, and in turn stronger support for compensations (Nooitgedagt et al., 2021). In Western Europe, autochthony beliefs were associated with outgroup prejudice (Martinović & Verkuyten, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Related research has shown that when historical atrocities are framed as contributing to the ongoing suffering of victimized groups, perpetrator groups report greater willingness to make amends (Imhoff et al, 2013). Similarly, among Anglo‐Celtic Australians (i.e., the settler majority group), it was found that recognizing the territorial ownership of Indigenous populations in the country was linked to greater guilt and shame over the atrocities that Anglo‐Celtic groups perpetrated against Aboriginal groups, which in turn explained support for reparations (Nooitgedagt et al, 2021). In settler colonial countries like Australia, cultural continuity for Indigenous groups is particularly consequential because there is ongoing erasure and silencing of the group's cultural traditions and histories (e.g., Anderson & Metzger, 2011; Brown & Brown, 2010; Short, 2005; Stastny, 2019).…”
Section: Historical Recognition Of Colonialismmentioning
confidence: 99%